2018
DOI: 10.1016/j.jviromet.2018.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Droplet digital PCR for absolute quantification of proviral load of human T-cell lymphotropic virus (HTLV) types 1 and 2

Abstract: The ddPCR reliably quantified HTLV DNA in clinical samples and could be a useful tool for monitoring of PVLs in HTLV-infected individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 19 publications
0
5
0
1
Order By: Relevance
“…Apart from a few exceptions, the ddPCR showed relatively low intra-/inter-assay CV, as the variance among replicates approached the mean over replicates (Brunetto et al, 2014;Liu et al, 2019). Results indicate that our ddPCR can provide a repeatable and reproducible quantification of HPV DNA, whereas it can be potentially used for patient longitudinal monitoring, given that HPV clearance is recorded over time (Thulin Hedberg et al, 2018). Following ddPCR set up, as first approach on biological/clinical samples, we extended the assay on restriction enzyme-undigested DNA isolated from 45 CIN tissues and 4 human cells lines, including 3 HPV-positive cervical cancer cell lines.…”
Section: Discussionmentioning
confidence: 86%
“…Apart from a few exceptions, the ddPCR showed relatively low intra-/inter-assay CV, as the variance among replicates approached the mean over replicates (Brunetto et al, 2014;Liu et al, 2019). Results indicate that our ddPCR can provide a repeatable and reproducible quantification of HPV DNA, whereas it can be potentially used for patient longitudinal monitoring, given that HPV clearance is recorded over time (Thulin Hedberg et al, 2018). Following ddPCR set up, as first approach on biological/clinical samples, we extended the assay on restriction enzyme-undigested DNA isolated from 45 CIN tissues and 4 human cells lines, including 3 HPV-positive cervical cancer cell lines.…”
Section: Discussionmentioning
confidence: 86%
“…Quantification of PVL using ddPCR has been established for human retroviruses, wherein the PVL in HTLV1 infections was used as a marker of disease progression. 45 Based on the similarities in pathogenesis between HTLV and BLV, we optimized ddPCR for BLV in peripheral blood of naturally infected cattle and experimentally infected sheep. The resulting ddPCR was highly sensitive and specific for BLV from various infected animals, making it suitable for use in early detection, to clarify inconclusive samples analyzed by qPCR, as well as for PVL quantification.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to nucleic acid detection, ddPCR is a platform designed to provide high precision for quantification of target molecules because it carries out direct quantification without requiring a calibration curve. 17,45 In contrast, the rtPCR assays used widely in diagnostic laboratories around the world show significant variability in the measurement of the BLV proviral DNA copy number among laboratories, even when qPCR is performed by experienced staff. 28,32,40 We found that PVLs were not concordant between qPCR and ddPCR.…”
Section: Discussionmentioning
confidence: 99%
“…The coefficient of variation for the C q values found was low for intra‐ and inter‐assay. Lower provirus concentrations in these samples may be one of the possible factors for variability found (Thulin Hedberg et al 2018). HTLV‐1 DNA was detected in all of the 12 samples.…”
Section: Discussionmentioning
confidence: 99%